Monumental Women: Commemoration, Vocation, and Irish Migration at Notre Dame - Cummings, Kathleen Sprows (Irish theological quarterly, 2024)
Headlines about memorials tend to skew toward the negative, emphasizing the removal of controversial monuments. Yet there is a substantial generative aspect to conversations about representation in public landscapes. In my case, paying more attention to public landscapes at my home institution led to new insights about the history of the Sisters of the Holy Cross at the University of Notre Dame, founded by the Congregation of Holy Cross near South Bend, Indiana, in 1842. Framed around a discussion of Catholic sisters’ invisibility in Notre Dame’s campus architecture, this article centers on a ‘questing’ trip Holy Cross superior Mother Angela Gillespie took to Ireland in 1873 in search of new members. It examines what precipitated Gillespie’s journey, what the subsequent arrival of some 40 postulants portended for Catholic America, and what themes and approaches it might suggest for the larger historical study of Catholic sisters at a pivotal historiographical moment.